Efficient CO catalytic oxidation by the combination of cobalt and excellent carrier Ta2O5 - Qin, Haijian; Wang, Huaibiao; Xia, Qing; Zheng, Chunzhi; Zhang, Xiaonan; Wu, You; Peng, Lei; Yang, Fengli; Zhao, Songjian (Fuel (Guildford), 2023)
Small size cobalt nanoparticles are highly dispersed on different crystalline forms of Ta2O5 (amorphous, T, M, H) by impregnation method, which is then introduced to catalytic oxidation of CO. The experimental results show that Co3O4/M-Ta2O5 exhibits the highest CO conversion efficiency compared with Co3O4 loaded on amorphous-, T-, and H-Ta2O5, and the pure Co3O4 and M-Ta2O5. The temperature of 90 % CO conversion rate is approximately 170 °C at the high space velocity of 780,000 h−1. Besides, the effect of oxygen concentration, space velocity, CO concentration, as well as different ratio of Co: Ta on CO conversion have been studied. Moreover, XRD, SEM, TGA, BET and H2-TPR characterizations reveal that Co3O4 is uniformly distributed and does not change the structure crystalline of Ta2O5, and there is strong interaction between cobalt active component and Ta2O5 support, which might be beneficial for CO conversion. Furthermore, the reaction mechanism has been investigated by X-ray photon spectroscopy and in-situ diffuse reflectance infrared Fourier transform spectroscopy (DRIFTs), which suggest that Co3+ is the active component and lattice oxygen as well as adsorbed oxygen play a critical role in CO oxidation.